A Review of the Importance of Peer Instruction Argumentative Strategy (PIAS) in Science Learning - Aina Jacob Kola (ÜNİVERSİTEPARK Limited, 2017)
The paper believes the method a teacher employed in science class for instruction makes students' learning difficult. A literature review of some common methods of teaching in science was done. The paper highlighted the conceptual framework of the Peer Instruction Argumentative Strategy (PIAS) and discussed the importance of PIAS to science learning. The paper recommended PIAS for science education classes based on its perceived advantages over the other teaching strategies.